2022
DOI: 10.3389/fcimb.2022.1055117
|View full text |Cite
|
Sign up to set email alerts
|

Association of general health and lifestyle factors with the salivary microbiota – Lessons learned from the ADDITION-PRO cohort

Abstract: IntroductionPrevious research indicates that the salivary microbiota may be a biomarker of oral as well as systemic disease. However, clarifying the potential bias from general health status and lifestyle-associated factors is a prerequisite of using the salivary microbiota for screening.Materials & MethodsADDDITION-PRO is a nationwide Danish cohort, nested within the Danish arm of the Anglo-Danish-Dutch Study of Intensive treatment in People with Screen-Detected Diabetes in Primary Care. Saliva sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 67 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…In addition, the genetic variant rs197620 was associated with higher risk of periodontitis and the genetic variant rs17793860 was associated with lower risk of stroke. In a recent study from our group, Poulsen et al showed a positive association between abundance of Rothia and glycosylated hemoglobin levels 34 . Other investigators showed that abundance of Rothia associate to childhood dental caries 23 , and history of colorectal cancer 35 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition, the genetic variant rs197620 was associated with higher risk of periodontitis and the genetic variant rs17793860 was associated with lower risk of stroke. In a recent study from our group, Poulsen et al showed a positive association between abundance of Rothia and glycosylated hemoglobin levels 34 . Other investigators showed that abundance of Rothia associate to childhood dental caries 23 , and history of colorectal cancer 35 .…”
Section: Discussionmentioning
confidence: 78%
“…A detailed description of saliva sample collection has been provided in a recent publication 34 . In brief, saliva was collected from 786 participants at Steno Diabetes Center Copenhagen, Copenhagen, Denmark.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Screening of articles by title and abstract and reviewing of full text resulted in 36 eligible articles for full text ( Figure 1 ). Of the 36 articles, nine were from the United States of America ( 18 26 ), six were from India ( 15 , 27 31 ), five were from the United Arab Emirates ( 32 36 ),three were from China ( 37 39 ), two from Japan ( 40 , 41 ) and others including Brazil ( 42 ), Jordan ( 43 ), Hungary ( 44 ), Croatia ( 45 ), Iran ( 46 ), Germany ( 47 ), Denmark ( 48 ), Italy ( 49 ), Sudan ( 50 ), Ireland ( 51 ) and Korea ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prevotella and Veillonella, mostly independently, were also found as predominant genus in tobacco users (21, 24, 31, 34, 37, 38, 42-44, 49, 51), while another data reported a significant depletion in the saliva and supragingival plaques of smokeless tobacco users (50). Neisseria was also observed to be higher among other genera in smokers in two studies conducted in China and Denmark (38,48). The detailed findings are presented in Table 2.…”
Section: Differences In the Abundance Of Various Taxa Between Smokers...mentioning
confidence: 92%
“…Notably, most patients had either not been treated for periodontal disease in a year or more prior, or had never received any form of periodontal therapy at all. Important confounders of saliva microbiome diversity, active caries, periodontal disease and antibiotic usage had been adjusted and controlled for, and the other contributors to taxa diversity, such as tobacco usage (estimated at 3% of the variability of the saliva microbiome) were also considered ( Belstrøm, 2020 ; Poulsen et al, 2022 ; Stewart et al, 2018 ). Diet, which is thought to contribute though to a lesser degree to the oral microbiome makeup, was not monitored ( Wade, 2021 ; Wells et al, 2022 ) ( Sekundo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%